The Impact of Rubber Price Fluctuations on Community Welfare and Consumption Patterns in Rengas 1 Village, Payaraman District, Ogan Ilir Regency from an Islamic Economic Perspective - Salsa Putri, Mei; Fiandi, Mufti; Septiatin , Aziz (CV. Era Digital Nusantara, 2024)
This research aims to determine the impact of rubber price fluctuations on welfare and consumption patterns in Rengas 1 village, Payaraman subdistrict, Ogan Ilir district from an Islamic economic perspective. This includes prices, welfare and consumption according to an Islamic economic perspective. This type of research is field research with a qualitative descriptive approach. Types of research data: primary data and secondary data. Data collection techniques through observation, interviews, documentation. Data analysis techniques for data reduction, data presentation, and drawing conclusions. Rubber farmer research respondents. The results of this research are that as a result of fluctuations in the price of rubber, people's income is unstable, so their interest in buying is reduced, they have difficulty continuing their children's education, they are in debt at the bank, as a result , the welfare of the people of Rengas 1 village cannot be met, so they cannot be said to be prosperous but are included in the pre-prosperous community group. . The welfare and consumption patterns of the people of Rengas 1 village are in accordance with Islamic law. The income obtained is used in accordance with Islamic law and is obtained through halal business and used in a halal way.